2015
DOI: 10.1063/1.4929983
|View full text |Cite
|
Sign up to set email alerts
|

Dependence of optimal spacing on applied field in ungated field emitter arrays

Abstract: In ungated field emitter arrays, the field enhancement factor β of each emitter tip is reduced below the value it would have in isolation due to the presence of adjacent emitters, an effect known as shielding or screening. Reducing the distance b between emitters increases the density of emission sites, but also reduces the emission per site, leading to the existence of an optimal spacing that maximizes the array current. Most researchers have identified that this optimal spacing is comparable to the emitter h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
29
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 34 publications
2
29
0
Order By: Relevance
“…As an example, recently, Forbes has shown that the rate at which the FEF from a pair of spherical emitters tend toward the FEF of a single sphere is given by a power law decay as a function of the separation center to center [16]. Prior to his work, many authors were assuming an exponential-type decay [17][18][19][20][21][22]. This power law was an important realization in the physical mechanism governing the FEF.…”
Section: Introductionmentioning
confidence: 99%
“…As an example, recently, Forbes has shown that the rate at which the FEF from a pair of spherical emitters tend toward the FEF of a single sphere is given by a power law decay as a function of the separation center to center [16]. Prior to his work, many authors were assuming an exponential-type decay [17][18][19][20][21][22]. This power law was an important realization in the physical mechanism governing the FEF.…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16][17][18][19] We can analyze these geometries in terms of nearest-neighbor emitter attributes by comparing each of the four configurations considered in this paper. Notably, linear and square arrays, quite obviously, share common geometrical attributes that influence the overall field enhancement of the arrays.…”
Section: Aip Advances 6 095007 (2016)mentioning
confidence: 99%
“…Hence, in previous work, we explored the emission characteristics of two-and four-fiber arrays of carbon emitters in a carefully prepared, simple geometry. [13][14][15][16][17][18][19] Our configuration allows a much more pristine and straightforward experimental geometry for isolating and interpreting the electric field screening from other effects such as work function variation across the cathode surface or statistical inhomogeneities in the geometry of the individual emitters that comprise the array.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Forbes [1] proved that, in the "floating sphere at emitter-plane potential (FSEPP)" model, at sufficiently large separations c between the sphere centres, the fractional reduction ρ in apex FEF falls off with a power law decay of c −3 , rather than the exponential decay usually assumed (e.g. [3][4][5]) prior to this work. This means that the interaction effect (which is a form of electrostatic depolarization) persists to larger separations than originally assumed.…”
mentioning
confidence: 90%